Hospital Staffing, Communication and Management on Patient Safety Rating at Dr. Iskak Hospital Tulungagung - Dara Benedicta Antoninda; Gancar Candra Premananto; Indasah (Universitas STRADA Indonesia, 2023)
Background: Patient safety is an important element of the quality of a health service, with the existence of a patient safety culture it is hoped that it can make patient care safer. Thus it is necessary to improve quality through several supporting aspects of patient safety. Purpose: The purpose of this study is to analyze staffing, communication and hospital management for patient safety ratings at Dr. Iskak Tulungagung Hospital. Methods: The type of research conducted in this activity is an observational study with a cross-sectional design and using logistic regression statistical tests. The sample in this study were 406 respondents. Results: Based on the characteristics of the respondents, it shows that nurses with an education level of S1 Nursing are 258 respondents and D3 Nursing are 148 respondents, with an age range > 41 years (38%), ages 31-40 years (36.7%), ages 20-30 years (25.3%), and the majority of nurses have working hours > 40 hours/week (75%) and working hours of 30-40 hours/week (25%). The results of the descriptive analysis show that the value of good category staffing is 95%, communication openness is good category is 87% and hospital management is good category is 92%. Meanwhile, based on the statistical test results, the p-value is 0.000 <0.05; p-value 0.000 <0.05; and a p-value of 0.000 <0.05. Conclusion: Thus indicating that there is the Influence of Hospital Staffing, Communication and Management on Patient Safety Rating at Dr.Iskak Hospital Tulungagung.